Penggunaan New Media di Kalangan Orang Tua Golongan Millenial sebagai Media Pola Asuh Anak Masa Kini di Era Digital - Fajrur, Muhammad; Febriana, Poppy (THUFULA, 2022)
Abstract : THE USE OF NEW MEDIA IN MILLENIAL PARENTS AS THE MEDIA FOR PARENTING .There has been a shift when parents get more access to information about parenting science from new media. Access to information in the world of parenting, which used to be only in the offline sphere, is now in the online realm. This qualitative method aims to obtain information about how parents educate their children in today's digital era. Data were collected through observation or interviews with several parents belonging to the millennial group. The results of this study can be seen that there has been a shift in sources of information on the values of parenting carried out by a number of parents of today's millennial groups who used to often get information about the values of parenting from their parents, in-laws, and several other elders. Currently, young parents of the millennial group actually get information about parenting values from the media. Parents also apply effective parenting if parents know what to do to educate children in the digital era which include: parents need to know and understand children's eye health, parents need to accompany children as digital generations and use digital media according to age and age. child development stage.Keywords: Social media, Parenting, New media, Children in the digital era